2019
DOI: 10.1111/cea.13338
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a naïve CD8+ T cell repertoire for benzylpenicillin

Abstract: Background: Beta-lactams allergy is the most commonly reported drug allergy and constitutes an important health problem. We previously showed the pre-existence of a naïve CD4+ T cell repertoire for benzylpenicillin (BP) coupled to human serum albumin (HSA) but little is known about the naïve CD8+ T cell repertoire specific for BP.Objective: The purpose of this work was to identify naïve CD8+ T cells specific for BP and to explore mechanisms dictating their activation.Methods: Co-cultures were established with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Previous works performed on nickel allergic patients showed a frequency of nearly 100 to 1,000-fold higher than our findings (34). However, the frequencies of naïve T cells recognizing benzylpenicillin (BP) (39, 45, 46) and immunogenic therapeutic antibodies (40) in non-immunized individuals were in the same range as those found in our study. It is important to note that the frequency of nickel-recognizing naïve T cells that we identified could still be an underestimation because of the use of nickel-loaded DCs, whereas it was shown that the activation of some nickel-specific T-cell lines (such as clone SE9) requires the persistent presence of nickel in the culture medium (20).…”
Section: Discussionsupporting
confidence: 79%
“…Previous works performed on nickel allergic patients showed a frequency of nearly 100 to 1,000-fold higher than our findings (34). However, the frequencies of naïve T cells recognizing benzylpenicillin (BP) (39, 45, 46) and immunogenic therapeutic antibodies (40) in non-immunized individuals were in the same range as those found in our study. It is important to note that the frequency of nickel-recognizing naïve T cells that we identified could still be an underestimation because of the use of nickel-loaded DCs, whereas it was shown that the activation of some nickel-specific T-cell lines (such as clone SE9) requires the persistent presence of nickel in the culture medium (20).…”
Section: Discussionsupporting
confidence: 79%
“…A study has identified two target peptides of human serum albumin (HSA) for benzylpenicillin, to which this drug was covalently bound on lysines 159 and 525, which were able to induce specific proliferation of T cells from BL‐allergic patients . Another study has suggested that patients could be immunized by benzylpenicillin‐haptenated peptides from proteins generated in dendritic cells during the processing and presentation to T cells . Moreover, CLV binds to Lys 195 and 475 residues of HSA, forming adducts able to activate basophils in 69% of CLV‐allergic patients .…”
Section: New Understanding Of Dhr Mechanismmentioning
confidence: 99%
“…140 Another study has suggested that patients could be immunized by benzylpenicillin-haptenated peptides from proteins generated in dendritic cells during the processing and presentation to T cells. 141 Moreover, CLV binds to Lys 195 and 475 residues of HSA, forming adducts able to activate basophils in 69% of CLV-allergic patients. 120…”
Section: Ige-mediated Reactionsmentioning
confidence: 99%
“…Previous studies with PBMCs from tolerant donors have reported a repertoire of naïve CD4 + and CD8 + T-cells that can be activated with benzylpenicillin. [15][16][17] This observation may be related to the fact that most of the general population in Europe has been exposed to BL antibiotics throughout their life. This exposure could also explain the detection of AX-specific T-cell clones in Clav-allergic patients and vice versa, that could be reinforced by the fact that both drugs are administered simultaneously in therapeutical treatments.…”
Section: Discussionmentioning
confidence: 99%